Analysis of factors associated with excess weight in school children - Renata Paulino Pinto; Altacílio Aparecido Nunes; Luane Marques de Mello
Abstract Objective: To determine the prevalence of overweight and obesity in schoolchildren aged 10 to 16 years and its association with dietary and behavioral factors. Methods: Cross-sectional study that evaluated 505 adolescents using a structured questionnaire and anthropometric data. The data was analyzed through the T Test for independent samples and Mann-Whitney Test to compare means and medians, respectively, and Chi2 Test for proportions. Prevalence ratio (RP) and the 95% confidence interval was used to estimate the degree of association between variables. The logistic regression was employed to adjust the estimates to confounding factors. The significance level of 5% was considered for all analysis. Results: Excess weight was observed in 30.9% of the schoolchildren: 18.2% of overweight and 12.7% of obesity. There was no association between weight alterations and dietary/behavioral habits in the bivariate and multivariate analyses. However, associations were observed in relation to gender. Daily consumption of sweets [PR=0.75 (0.64-0.88)] and soft drinks [PR=0.82 (0.70-0.97)] was less frequent among boys; having lunch daily was slightly more often reported by boys [OR=1.11 (1.02-1.22)]. Physical activity practice of (≥3 times/week) was more often mentioned by boys and the association measures disclosed two-fold more physical activity in this group [PR=2.04 (1.56-2.67)] when compared to girls. Approximately 30% of boys and 40% of girls stated they did not perform activities requiring energy expenditure during free periods, with boys being 32% less idle than girls [PR=0.68 (0.60-0.76)]. Conclusions: A high prevalence of both overweight and obesity was observed, as well as unhealthy habits in the study population, regardless of the presence of weight alterations. Health promotion strategies in schools should be encouraged, in order to promote healthy habits and behaviors among all students.